PENGARUH VARIASI LATIHAN LONG PASSING TERHADAP KETEPATAN LONG PASSING PEMAIN SEPAKBOLA WOMEN SOCCER JAMBI FC - Findi Yenita Sari; Muhammad Ali; Hendri Munar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Based on initial observations often show that female soccer players, including in the Jambi FC Women Soccer squad, still face obstacles in the consistency and accuracy of long passing. Initial observations show that Jambi FC Women Soccer football has often done long passing exercises. The purpose of this study is to determine the effect of variations in long passing exercises on the accuracy of long passing of Jambi FC Women Soccer football players. This study uses an experimental method, in this study there is one experimental group that is deliberately given treatment. The sample in this study were 16 players aged 15 to 17 years old. The results obtained from the initial test of long passing accuracy obtained an average of 169.38 standard deviation 37.854 with the best long passing accuracy getting a score of 230 and the lowest long passing accuracy getting a score of 120. The initial test of long passing accuracy obtained an average of 235.00 Standard Deviation 33.267 with the lowest long passing accuracy of 180 and the best long passing accuracy of 300. The results of data analysis obtained a significant value for pre-test and post-test data 0.200 > 0.05. Based on this data analysis, it can be concluded that the pre-test and post-test data are normally distributed, with a significance value of (0.533) > (0.05). Therefore, the analysis results indicate that the data vary homogeneously. The t-test shows a significance value of 0.00 < 0.05, and a calculated t-value of 7.190 > 1.753 (t-table). It can be concluded that there is an effect of variations in long passing training on the accuracy of long passing of women's soccer players at Soccer Jambi FC.